COMPETENCY ANALYSIS OF EXTENSION OFFICERS IN AGRICULTURAL EXTENSION ACTIVITIES IN BANDA BARO SUB-DISTRICT, ACEH UTARA - Martina, Martina; Zuriani, Zuriani; Zahara, Hafni; Maulani, Cut; Rezeki, Vina (CV. Radja Publika, 2022)
The number of agricultural extension workers in Aceh Utara based on each sub-district is 279 people. Banda Baro sub-district is the sub-district that has the least number of extension workers among other sub-districts, namely 4 civil servants and 1 self-help extension with the target area consisting of 9 villages. The limited number of extension workers makes it difficult for extension workers to meet extension workers directly and the difficulty of communication networks so that it affects the competence of extension workers in extension activities. This study aims to analyze the competence of extension workers in agricultural extension activities in Banda Baro Sub-District, Aceh Utara. The number of research samples was 105 farmers and the types of data used were primary and secondary data. The data were analyzed descriptively qualitatively which was measured using a Likert scale. The results showed that the average competency of the instructor in extension activities was in the competent category with an index of 77.89%, meaning that the extension worker had good competence in communicating with farmers, planning programs, implementing programs, using methods, building an entrepreneurial spirit, building networking, and evaluating programs